2022
DOI: 10.1186/s12902-022-01040-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of a disease management program to prevent diabetic nephropathy: a propensity score matching analysis using administrative data in Japan

Abstract: Background Existing reviews indicated that disease management for patients with diabetes may be effective in achieving better health outcomes with less resource utilization in the short term. However, the long-term results were inconsistent because of the heterogeneous nature of the study designs. In the present study, we evaluated the 5-year follow-up results of a local disease management program focused on diabetic nephropathy prevention under the universal public health insurance scheme in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Public medical insurance providers, including local governments, who provide enrolees with the opportunity to opt-out (passive consent), are able to utilize anonymized data without data linkage in collaboration with academic and research organizations, solely for getting valuable information to maintain and improve enrolees’ wellness [ 26 ]. Under this process, the limited long-term effect of a local government health program on medical cost reduction was reported [ 26 ]. The nationwide SHC program has been required to be offered by law since 2008, but a recent report indicated that it had no effect on improving or maintaining laboratory values [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Public medical insurance providers, including local governments, who provide enrolees with the opportunity to opt-out (passive consent), are able to utilize anonymized data without data linkage in collaboration with academic and research organizations, solely for getting valuable information to maintain and improve enrolees’ wellness [ 26 ]. Under this process, the limited long-term effect of a local government health program on medical cost reduction was reported [ 26 ]. The nationwide SHC program has been required to be offered by law since 2008, but a recent report indicated that it had no effect on improving or maintaining laboratory values [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by the higher frequency of outpatient visits among CDMP participants. Under Japan's universal public health insurance system, a five-year follow-up of local disease management programs, including patient education programs with a focus on preventing diabetic complications, showed that these programs were somewhat effective in reducing diabetic complications and the need for emergency care [ 27 ]. In a retrospective chart review conducted in the United States and published in 2022, the effects of comprehensive diabetes education on the reduction of glycated hemoglobin (HbA1c) and fasting blood glucose were reported [ 8 ].…”
Section: Discussionmentioning
confidence: 99%